IMPROVING RUSSIA’S POSITION IN BUSINESS ENVIRONMENT RATINGS AS THE PROBLEM OF STATE POLICY - A. Bukova (Publishing House of the State University of Management, 2016)
International ratings let compare various aspects of social life in the country or region: economic development, business operating conditions, the effectiveness of public administration and others. In Russia in recent years, interest in international ratings in the economic and business climate is constantly growing. The article defines the international independent ratings regularly calculated by international rating agencies and financial institutions. The position in these ratings represents an important element of the international image of the state. In addition, the place and the dynamics of Russian indicators are shown in the article.